2023
DOI: 10.2174/1570180819666220615092854
|View full text |Cite
|
Sign up to set email alerts
|

Phytosome: An Effective Transdermal Drug Delivery System for Phytoconstituents

Abstract: Herbal medicine and phytochemicals have always been great therapeutic options to treat various diseases due to their compatibility, safety, easy production, low cost and side effects. However, low absorption rate ,and poor bioavailability are notable challenges that have limited the use of most phytoconstituents. To address these challenges, different drug delivery methods have been proposed for generating operative carrier systems for phytochemicals. Among them, transdermal drug delivery (TDD) using nanophyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…[44][45][46][47] Our results, thus, showed that these beneficial effects could be increased through phytosomal formulation. Previous studies have also indicated that phosphatidylcholine in the phytosome not only carries biologically active flavonoids, but also acts as a biologically active nutrient for liver disease, including alcoholic hepatic steatosis 48,49 ; moreover, plant extracts in phytosomes are protected against degradation by gastrointestinal secretions and intestinal bacteria due to their lipid-resistant bond. 50 In this regard, serum analysis of 23 healthy individuals that used silybinphosphatidylcholine (silibinin is the primary active flavonolignan in silymarin extract) or silymarin showed the higher bioavailability of silybin-phosphatidylcholine when compared to silymarin.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46][47] Our results, thus, showed that these beneficial effects could be increased through phytosomal formulation. Previous studies have also indicated that phosphatidylcholine in the phytosome not only carries biologically active flavonoids, but also acts as a biologically active nutrient for liver disease, including alcoholic hepatic steatosis 48,49 ; moreover, plant extracts in phytosomes are protected against degradation by gastrointestinal secretions and intestinal bacteria due to their lipid-resistant bond. 50 In this regard, serum analysis of 23 healthy individuals that used silybinphosphatidylcholine (silibinin is the primary active flavonolignan in silymarin extract) or silymarin showed the higher bioavailability of silybin-phosphatidylcholine when compared to silymarin.…”
Section: Discussionmentioning
confidence: 99%
“…Nano, meaning "dwarf " in Greek, involves particles ranging from 1 to 100 nm in size (Demir, 2020;Hasan and Raheem, 2021). Phytosome, an advanced drug delivery system, is an evolved form of liposome particles and herbal formulation, it comprises phytoconstituents from plant extracts enclosed by a lipid layer (Mahmoudabad et al, 2023;Eftekhari et al, 2023). This system heightens the bioavailability of water-soluble phytoconstituents by enveloping them with phospholipids, leading to improved absorption in the intestinal lumen through simple diffusion.…”
Section: Advances Inmentioning
confidence: 99%